2020
DOI: 10.3233/jad-200413
|View full text |Cite|
|
Sign up to set email alerts
|

An Immunomodulatory Therapeutic Vaccine Targeting Oligomeric Amyloid-β1

Abstract: Background: Aging is considered the most important risk factor for Alzheimer’s disease (AD). Recent research supports the theory that immunotherapy targeting the “oligomeric” forms of amyloid-β (Aβ) may halt the progression of AD. However, previous clinical trial of the vaccine against Aβ, called AN1792, was suspended due to cases of meningoencephalitis in patients. Objective: To develop a peptide sensitized dendritic cells (DCs) vaccine that would target oligomer Aβ and prevent an autoimmune response. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In this regard, a recent study in the APP/PS1 mouse model of AD showed that injection of dendritic cells presenting a modified Aβ peptide triggered a specific antibody response and improved memory performance to a similar degree than that exhibited by non-transgenic, untreated mice. Importantly, the vaccine did not trigger an inflammatory response [ 70 ]. Despite past failures and the significant challenge involved in developing and testing vaccines against endogenous neurodegenerative disease proteins, these sustained efforts to harness the immune system to treat AD will hopefully bring long-awaited success.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a recent study in the APP/PS1 mouse model of AD showed that injection of dendritic cells presenting a modified Aβ peptide triggered a specific antibody response and improved memory performance to a similar degree than that exhibited by non-transgenic, untreated mice. Importantly, the vaccine did not trigger an inflammatory response [ 70 ]. Despite past failures and the significant challenge involved in developing and testing vaccines against endogenous neurodegenerative disease proteins, these sustained efforts to harness the immune system to treat AD will hopefully bring long-awaited success.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of AD is complex which is characterized by a progressive loss of neurons and involves Aβ plaques formation, activation of astrocytes and microglia (Guo et al, 2020;Tiwari et al, 2019). Vaccines and active immunotherapy are being studied against AD (Bittar et al, 2018;Song et al, 2020). The aim of this study was to investigate Aβ plaques and changes of astroglia and microglia in mice injected with a new vaccine based on Aβ3-10 as the antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Some strategies for AD treatment aim to consolidate the clearance of Aβ plaque and elimination of neuroinflammation reactions (Lemere, 2013), and immunotherapy against Aβ and phosphorylated tau (p-Tau) has been suggested for more than 20 years. Pre-clinical studies have shown some efficacy of vaccines and active immunotherapies against Aβ and p-Tau, but the translation to humans proved ineffective and with serious safety issues (Song et al, 2020). Among others, a vaccine against Aβ1-42 (Elan Pharmaceuticals, CA, USA) could remove amyloid plaques and improve perceptive function in transgenic animal models and AD patients (Janus et al, 2000;Vellas et al, 2009), but the clinical trial of the Aβ1-42 vaccine was suspended because of severe side effects like acute meningoencephalitis and cerebral hemorrhage (Rosenberg, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major focuses of drug discovery efforts in the AD area has been the development of drug candidates to regulate abnormal Aβ aggregation. Several synthetic drugs have been evaluated in clinical trials, including LY2886721 [ 113 ], AN1792 [ 114 ] and verubecestat [ 115 ], along with monoclonal antibody drugs such as donanemab, which targets Aβ 3–42 [ 116 ] and aducanumab (BIIB037), which targets a conformational epitope found on Aβ [ 117 ]. However, none of them have been successful in the treatment of AD.…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%